Evaluation of the Main Causes of Diesel Engine Injector Failure using Fault Tree Analysis - Matar, Hanan B.; Al-Zubaidi, Sawsan S.; Al-Kindi, Luma A. (Al-Khwarizmi Engineering Journal, 2021)
The maintenance of the diesel engine parts in any electric power station contains many problems that lead to stopping. Several reasons lead to such problems; these reasons should be analyzed and evaluated in order to eliminate their effects. This paper is based on evaluation of the main causes that lead to diesel engine injector failure as a main part of electric power stations, using fault tree analysis (FTA). The FTA is the most broadly utilized strategies in the industrial area to perform reliability analysis of complex designing frameworks. A fault tree is a logical representation of the relationship of basic events that lead to a given unwanted event (i.e., top event). Starting with introducing the FTA and how it could be utilized in analyzing the reasons of main issues that lead to that the injector stops working, in which the probability of occurrence of each issue is calculated. The application of the root cause analysis principle of diesel engine injector failure in diesels Haditha station is chosen as a case under study. According to the probabilities’ evaluation by using the FTA based on of the causes under the top event its value was (0.80). It is concluded from the analysis that the three largest values of the occurrence of a problem with the diesel engine injector are 0.50 for fuel problems, 0.20 for overloads, and 0.18 for nozzle head corrosion. Plant management can define a specific plan with taking into consideration the calculated value of each cause in order to reduce their impacts and to avoid long downtime hours compared to operating hours. Finally, recommandations are suggested to overcome these causes.